A Case of Complicated Acute Type B Aortic Dissection - Chowdhury, Mashhud Zia; Ghafoor, Nusrat; Salauddin, Mohammed; Iqbal, Md Jabed; Siddiqui, Md Mahmudur Rahman (Anwer Khan Modern Medical College Journal, 2015)
A 65 year lady with chest and back pain was referred to our hospital with suspected case of acute coronary syndrome. A computed tomography (CT) aortic angiogram showed dissection of abdominal and thoracic aorta. Patient was initially treated by drugs for controlling heart rate and blood pressure with analgesics but due to progression of disease and involvement of left subclavian artery ostium referred for surgical intervention. She underwent left carotid-subclavian bypass and TEVAR (Thoracic endovascular aortic repair) with good outcome. The present case is a good demonstration revealing that in absence of clinical suspicion and diagnostic imaging, acute aortic dissection represents a diagnostic dilemma which requires immediate action. Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 46-49